Kennings as Blends and Prisms - Broz, Vlatko (Array, 2011)
This paper argues that recent advances in cognitive linguistics could shed more light onto solving a particular historical semantics problem, namely the semantics of kennings in Beowulf. The well-known figures of speech are very difficult to understand because of a rather enigmatic way of making reference to people or things (Brodeur 1960 ; Wehlau 1997). The first part of the paper aims to define the kenning as a particular type of compound to set it apart from ordinary compounds. The second and third parts of the paper apply recent cognitive linguistic ap-proaches to semantic compositionality, treating kennings as composite expres-sions whose meaning is derived from an intricate interaction of metonymy and metaphor. For the purpose of a semantic analysis of kennings, a few of the best known examples have been selected. They are analysed first within the framework of mental space and blending theory (Fauconnier and Turner 1998 and 2002), and then they are analysed applying the prismatic model (Geeraerts 2002).